2017
DOI: 10.1186/s12929-017-0327-y
|View full text |Cite
|
Sign up to set email alerts
|

ALDH2 polymorphism and alcohol-related cancers in Asians: a public health perspective

Abstract: The occurrence of more than 200 diseases, including cancer, can be attributed to alcohol drinking. The global cancer deaths attributed to alcohol-consumption rose from 243,000 in 1990 to 337,400 in 2010. In 2010, cancer deaths due to alcohol consumption accounted for 4.2% of all cancer deaths. Strong epidemiological evidence has established the causal role of alcohol in the development of various cancers, including esophageal cancer, head and neck cancer, liver cancer, breast cancer, and colorectal cancer. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
165
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(169 citation statements)
references
References 67 publications
3
165
1
Order By: Relevance
“…The misclassification accounts for the weaker or nonsignificant association of EC with facial flushing than with ALDH2 genotype, as shown in our study and previous studies . When using flushing response for screening and prevention counseling, the high false‐negative rate should be particularly cautious among regular alcohol consumers, in which heterozygous carriers has risen substantially in the last few decades …”
Section: Discussionmentioning
confidence: 99%
“…The misclassification accounts for the weaker or nonsignificant association of EC with facial flushing than with ALDH2 genotype, as shown in our study and previous studies . When using flushing response for screening and prevention counseling, the high false‐negative rate should be particularly cautious among regular alcohol consumers, in which heterozygous carriers has risen substantially in the last few decades …”
Section: Discussionmentioning
confidence: 99%
“…ALDH2 is a key metabolic enzyme in the mitochondria, which not only metabolizes aldehyde into acetic acid, but also detoxifies toxic aldehyde substances such as 4‐HNE and MDA . Several studies have revealed the protective role of ALDH2 in alcoholic liver cirrhosis and liver cancer . Given that nearly half of the East Asian population possessed the loss‐of‐function mutation of ALDH2, the role of ALDH2 in liver fibrosis still needs further elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies suggest that the ethanol (but not the other components of alcoholic beverages) matters primarily for cancer risk, regardless of the types of alcoholic beverages . In addition, we could not assess other explanatory variables such as menopausal hormone therapy (for female breast cancer), a family history of cancer, diet (eg, coffee and red meat), physical activities, and ALDH2 genotypes . In the JPHC study, alcohol‐related bladder cancer risk was observed in male “flushers” (who are supposed to have polymorphisms in ALDH2 enzyme) but not in male nonflushers .…”
Section: Discussionmentioning
confidence: 99%
“…For example, alcohol use increases circulating sex hormone levels, and this contributes to excess breast cancer risk. 13 In addition, acetaldehyde, a metabolite of ethanol classified as a group 1 carcinogen by the International Agency for Research on Cancer, stimulates Cancer March 1, 2020 cell proliferation and induces DNA damage. [6][7][8][9][10]13,14 The Japanese have a higher prevalence of polymorphisms in the aldehyde dehydrogenase 2 (ALDH2) enzyme, which makes them slower at metabolizing acetaldehyde.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation